2006
DOI: 10.1523/jneurosci.3212-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Stable Rhodopsin/Arrestin Complex Leads to Retinal Degeneration in a Transgenic Mouse Model of Autosomal Dominant Retinitis Pigmentosa

Abstract: Over 100 rhodopsin mutation alleles have been associated with autosomal dominant retinitis pigmentosa (ADRP). These mutations appear to cause photoreceptor cell death through diverse molecular mechanisms. We show that K296E, a rhodopsin mutation associated with ADRP, forms a stable complex with arrestin that is toxic to mouse rod photoreceptors. This cell death pathway appears to be conserved from flies to mammals. A genetics approach to eliminate arrestin unmasked the constitutive activity of K296E and caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 62 publications
3
69
0
Order By: Relevance
“…Note that although the K296E mutant is associated with RP in humans, it did not by itself cause significant RD in these experiments. It is likely that RD would be observed at longer time points, or at higher expression levels (Chen et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that although the K296E mutant is associated with RP in humans, it did not by itself cause significant RD in these experiments. It is likely that RD would be observed at longer time points, or at higher expression levels (Chen et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The structural integrity of the N-terminus is sensitive to changes in amino acid sequence surrounding N2 and possibly dependent on the presence of the carbohydrate moiety itself at N15 (Tam and Moritz, 2009). In transgenic animals, P23H rhodopsin mislocalizes to inner segments (IS) and expresses at low levels (Roof et al, 1994;Moritz, 2006, 2007;Price et al, 2011;Sakami et al, 2011) and in cultured cells induces ER stress (Chiang et al, 2012), suggesting protein misfolding and degradation. In contrast, T4K and T17M rhodopsins express at high levels, exhibit little or no misfolding and localize primarily to the OS in transgenic frog rods suggesting that ER stress may not play a major role in their pathology.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that stable rhodopsin/arrestin complex is toxic to the mammalian retina in a cell death pathway that is conserved from flies to mice (11). To see whether endocytosis of K296E/ARR1 is involved in generating an apoptotic signaling pathway, we investigated the ability of ARR1 to bind AP-2, the adaptor protein central to coated pit formation (12,13).…”
Section: Resultsmentioning
confidence: 99%
“…The trigger that leads to the cell death resulting from endocytosis of Rh1/Arr2 complexes is still unknown. This issue may have bearing on human retinal dystrophies as the phenomenon of retinal degeneration resulting from stable rhodopsin/arrestin complexes has been documented in rodent animal models [236,237]. Mutations in Drosophila crumbs and its human homolog lead to light-induced retinal degeneration, but the mechanisms underlying these retinal degenerations are poorly understood [238,239].…”
Section: Discussionmentioning
confidence: 99%